Empirical Study on the Operational Status and Key Influencing Factors of Outpatient Multidisciplinary (MDT) Service Model: A Cross-Sectional Study in Sichuan Province, China - Wang H; He Q; Guo Y; Feng G; He X; Wan Z (Journal of Multidisciplinary Healthcare)
HuanLin Wang,1,2 Qian He,1,2 Yuan Guo,2 GuoWen Feng,1,2 Xuan He,1,2 Zhi Wan1,2 1Rare Diseases Center West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Outpatient West China Hospital of Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Zhi Wan, Email 303680215@qq.comBackground: Currently, there is a lack of baseline research on outpatient Multi-Disciplinary Team (MDT) services. Through conducting a cross-sectional survey in Sichuan Province, China, this study aims to explore the current status and influencing factors of outpatient MDT services, providing a reference for their further development.Methods: A questionnaire survey was conducted in June 2024 on tertiary medical institutions in Sichuan Province using the cluster sampling method. A total of 203 valid questionnaires were collected, yielding an effective response rate of 91.0%. Descriptive statistics, correlation, and difference tests were employed to analyze the survey data.Results: The development rate of outpatient MDT in tertiary medical institutions in Sichuan Province was 77.3%, and the start-up time was mainly concentrated in the past five years. About 87.3% of the hospitals set up fixed MDT teams with the number of ≤ 10, which was still in the development stage. In terms of MDT organization and management, 96.8% of the hospitals have issued relevant management systems, but the cognitive differences of MDT function positioning lead to significant heterogeneity in organization and management and operation mode. The analysis of key influencing factors shows that team dynamics is the primary internal driving factor, while medical insurance policy is the primary external influencing factor.Conclusion: Medical institutions need to promote the standardized development of outpatient MDT from the two dimensions of system construction and mechanism innovation: first, improve the institutionalized management framework: integrate the core link of MDT into the hospital quality management system through the construction of standardized workflow. Second, establish a refined assessment mechanism: focus on process indicators such as the standardized rate of case discussion and the implementation rate of the scheme, support an interdisciplinary performance incentive system, and mobilize the enthusiasm of departments and doctors to promote their rapid development.Keywords: multi-disciplinary team, outpatient MDT, current situation survey, influence factor